Melamine phosphite / aluminum phosphite with core-shell structure and preparation method thereof

Through the water heat method synthesize the melamine sub -phosphoric acid salt/aluminate composite material with a nuclear shell structure, it solves the problem of high temperature injection molding and layered in processing during processing during processing, which improves the decomposition temperature and decentralization. Flame retardant effect.

CN119371722AActive Publication Date: 2025-01-28SHENZHEN RUN SUN CHEM TECH

Patent Information

Application Number
CN202411661929.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-28
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

During the processing process, existing melamine-based flame retardants are prone to ammonia and corrosion of molds at high temperature injection molding, and have low stacking density, easy to delaminate with engineering plastics, poor processability and poor dispersion of resins.

Method used

Synthesis through the water heat method to synthesize the composite material of melamine sub -phosphoric acid salt/aluminum phosphate with a nuclear shell structure. The surface active agent is used to promote the formation of the nuclear shell structure. The melamine phosphoricate is nucleus. The temperature and time of the synthetic reaction control the thickness of the shell.

Benefits of technology

The decomposition temperature of the melamine -based flame retardant is increased, the ammonia gas release rate is reduced, the flame retardant effect of condensed phase is enhanced, and the dispersability is improved by controlling the particle size, which is suitable for various plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371722A_ABST
    Figure CN119371722A_ABST
Patent Text Reader

Abstract

The invention relates to melamine phosphite / aluminum phosphite with a core-shell structure and a preparation method of the melamine phosphite / aluminum phosphite, belongs to flame retardants, and in order to further improve the performance of a melamine-based flame retardant, melamine phosphite and aluminum phosphite are synthesized into a novel flame-retardant material with the core-shell structure through a hydrothermal method. Formation of a core-shell structure is promoted by using a surfactant. The preparation method disclosed by the invention has the beneficial effects that (1) the particle size D50 of the melamine phosphite can be controlled to be 0.8-2.0 microns through the quaternary ammonium salt type surfactant and the reaction temperature, so that the dispersity of the product is enhanced; (2) the thickness of a finished shell can be controlled, so that the decomposition temperature of a final product is increased, the decomposition temperature of the melamine-based flame retardant is increased from about 260 DEG C to 400-450 DEG C, and the particle size D50 of the product can be controlled to be 15-20 microns; and (3) the release rate of gas is effectively slowed down, and the gas-phase flame retardant effect of the melamine phosphite is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to flame retardants, and in particular relates to melamine phosphite / aluminum phosphite with a core-shell structure and a preparation method thereof. Background Art

[0002] The core-shell structure is an ordered assembly structure at the nanoscale formed by one nanomaterial encapsulating another nanomaterial through chemical bonds or other forces. Due to its unique structural characteristics, the core-shell structure integrates the properties of the two materials inside and outside, and complements each other's deficiencies. It has been an important research direction in recent years where morphology determines properties, and it has been enduring. With the continuous deepening of research on flame retardants applied to polymer materials, additive flame retardants are mainly divided into halogen flame retardants and halogen-free flame retardants, but halogen-based flame retardants are prone to release toxic and harmful gases and smoke, which have adverse effects on the environment. Melamine salt is an important component of halogen-free intumescent flame retardant, which is an intumescent flame retardant system integrating carbon source, acid source and gas source. Melamine nitrogen flame retardant is halogen-free, low smoke, stable to light and heat, has good flame retardant effect, and is cheap. In recent years, people have widely studied and applied halogen-free flame retardants such as melamine and its salts, and have prepared many melamine-based flame retardants with good performance, which have been applied in various polymer materials. Commonly used varieties include melamine, melamine urea cyanate (MCA), etc., which often need to be added with synergists and are used in resins such as PA, PU, ​​PO, PET, PS, and PVC. Nitrogen / phosphorus is the most commonly used synergistic flame retardant system. Aluminum phosphite is a new domestic inorganic phosphorus flame retardant with good dispersibility and good affinity with organic matrices. It helps to exert the excellent properties of organic materials and avoid local stress-induced material damage and failure. It is widely used as a single flame retardant or a compound flame retardant.

[0003] Since 2001, there have been many reports on the synthesis of phosphite microporous materials by hydrothermal methods. The reported phosphite microporous materials contain many transition metal phosphites, such as one-dimensional, two-dimensional, and three-dimensional zinc phosphites, organic template chromium fluorophosphites, inorganic-organic hybrid cobalt phosphites, three-dimensional iron phosphites, and vanadium phosphites. There are also reports on the use of polynitrogen compound guanidine carbonate as a structure-directing agent to synthesize aluminum phosphite [Al2(HPO3)3(H2O)3]·H2O (abbreviated as Al-7) crystals with a three-dimensional open skeleton and a three-dimensional cross-channel system of 10-membered rings, 8-membered rings, and 8-membered rings by hydrothermal methods. It has been confirmed that the structure of Al-7 does not contain guanidine carbonate as an organic template, indicating that guanidine carbonate may provide a certain reaction environment and pH value conditions for the synthesis of Al-7, rather than an organic template. This provides theoretical support for the preparation of aluminum phosphites with multidimensional skeleton structures under certain reaction environments and pH conditions.

[0004] Melamine and its salt flame retardants have multiple reaction functions. The composite system with nitrogen flame retardants has poor processability and poor dispersion with resin. Because melamine will decompose at around 260°C, there is a problem of ammonia gas being easily generated during high-temperature injection molding during processing, which can corrode the mold. In addition, the bulk density is low and it is easy to delaminate with engineering plastics. Summary of the invention

[0005] In order to further improve the performance of melamine-based flame retardants, the present invention synthesizes a new flame retardant material with a core-shell structure by a hydrothermal method from melamine phosphite and aluminum phosphite, and promotes the formation of the core-shell structure by using a surfactant. With melamine phosphite as the core, aluminum phosphite is deposited and attached to the surface of melamine to form a shell layer. After the reaction is completed, a white powder solid is obtained by washing, filtering, drying, baking and other steps, that is, a melamine phosphite / aluminum phosphite composite material with a core-shell structure. The above-mentioned preparation method specifically includes the following steps:

[0006] (1) Preparation of dilute melamine phosphite solution

[0007] Step 1.1), dissolving phosphorous acid or its salt in deionized water, heating and stirring, to obtain a phosphorous acid or its salt solution with a concentration of 30-50wt%;

[0008] The phosphorous acid or its salt is phosphorous acid (H3PO3) and its various phosphites, such as sodium phosphite (Na2HPO3) and ammonium phosphite ((NH4)2HPO3). The heating temperature is set at 70-80°C and the stirring speed is 12-17r / min.

[0009] Step 1.2), pouring melamine aqueous dispersion (dispersion ratio is 30-50wt%) into the above phosphorous acid or its salt solution in batches;

[0010] Generally speaking, each batch is added with a weight of 15-20wt% melamine aqueous dispersion. When adding each batch, continue to add after the solution becomes transparent, keep the mixed solution temperature at 70-80℃ and continue stirring, and add 1-5 parts by weight of quaternary ammonium salt surfactant during the reaction. After continuous stirring for 1-2h, the suspension gradually becomes viscous, add water and heat to 90-120℃, and the reaction is completed when the suspension becomes transparent. Pour in batches to complete the reaction and prevent agglomeration.

[0011] The quaternary ammonium salt surfactant includes one or a combination of two of hexadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, dodecyl dimethyl benzyl ammonium chloride and dialkyl dimethyl ammonium salts, and the addition amount of the quaternary ammonium salt surfactant is 1-5 wt %.

[0012] Step 1.3), after the obtained solution is completely cooled, it is filtered and washed until the pH value is neutral, and then dried to obtain melamine phosphite; the drying temperature is 90-120° C. and the drying time is 8-12 hours.

[0013] Step 1.4), dissolving the above melamine phosphite in an aqueous solution at 80-100° C. to prepare a 15-35% melamine phosphite dilute solution.

[0014] (2) Preparation of saturated aluminum phosphite solution

[0015] Step 2.1), dissolving phosphorous acid or its salt in a certain aqueous solution, wherein the concentration of the phosphorous acid or its salt solution is consistent with that in step 1.1).

[0016] Step 2.2), add the measured aluminum hydroxide to the above phosphorous acid or its salt solution concentration, start heating and stirring; the weight ratio of the aluminum hydroxide to the phosphorous acid or its salt is 0.5-0.8:1, the heating temperature is 70-100°C, and the stirring speed is 12-17r / min.

[0017] Step 2.3), adjust the above solution to a saturated solution state, and adjust the pH to 3-3.5;

[0018] Step 2.4), adding a dispersant to the saturated aluminum phosphite solution to maintain the stability of the saturated solution. The dispersant includes at least one of barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, copper stearate, vinyl bisstearamide, and tristearic acid glyceryl, and the addition amount is 0.2-2wt% (the weight occupied in the entire reaction system).

[0019] (3) Synthesis of melamine phosphite / aluminum phosphite with core-shell structure

[0020] Step 3.1), add the dilute melamine phosphite solution obtained in step (1) to the saturated aluminum phosphite solution in step (2), keep heating and stirring, the heating temperature is 80-100° C. The weight ratio of the dilute melamine phosphite solution to the saturated aluminum phosphite solution can be 1:1.5.

[0021] Step 3.2), adding a coupling agent to the above solution in an amount of 0.5-2wt% to promote the combination of aluminum phosphite and melamine phosphite. Under certain temperature conditions, aluminum phosphite gradually aggregates into a shell on the surface of melamine phosphite, and a white precipitate is produced after the reaction is complete;

[0022] The coupling agent includes at least one of silane coupling agents KH550, KH560, KH570, KH792, DL602 and DL171. The reaction temperature is 90-110° C. and stirring is continued until a white precipitate is generated.

[0023] Step 3.3), the obtained white precipitate is filtered, washed to pH 4.0-4.5, and dried to obtain a white precipitate; the drying temperature is 100-180° C., and the time is 5-8 h.

[0024] Step 3.4), the white precipitate is placed in a reactor with a polytetrafluoroethylene liner, and placed in a muffle furnace for baking to solidify the core-shell structure of melamine phosphite / aluminum phosphite; the baking temperature is 200-350° C., and the baking time is 3-5 hours.

[0025] Step 3.5), grind the obtained white powder, and screen to obtain melamine phosphite / aluminum phosphite with a core-shell structure.

[0026] The present invention synthesizes a novel flame retardant material with a core-shell structure by hydrothermal method from melamine phosphite and aluminum phosphite, with melamine phosphite as the core and aluminum phosphite deposited and attached to the surface of melamine phosphite to form a shell. The structural material can increase the decomposition temperature of the flame retardant by adjusting the temperature and time of the synthesis reaction to control the thickness of the shell, and slow down the release rate of ammonia gas from the thermal decomposition of melamine phosphite, thereby enhancing the flame retardant effect of the condensed phase. The particle size D of the flame retardant can also be adjusted by controlling the deposition time of aluminum phosphite. 50 The particle size of most flame retardants on the market is controlled at 15-20μm. 50 By controlling the particle size at 30-50μm, we can stabilize the particle size at a finer level, making the flame retardant more dispersible and easier to add and apply to various plastics.

[0027] Compared with the prior art, the present invention has the following advantages and effects:

[0028] (1) The particle size D50 of melamine phosphite can be controlled within 0.8-2.0 μm by using quaternary ammonium salt surfactant and reaction temperature, thus enhancing the dispersibility of the product;

[0029] (2) During the shelling process of melamine phosphite / aluminum phosphite, the thickness of the shell can be controlled by adjusting the reaction temperature and time, thereby increasing the decomposition temperature of the final product. The decomposition temperature of the melamine-based flame retardant can be increased from about 260°C to 400-450°C, and the particle size D of the product can be controlled. 50 At 15-20 μm;

[0030] (3) Melamine phosphite / aluminum phosphite with core-shell structure. The decomposition temperature of aluminum phosphite is higher than that of melamine phosphite. When melamine phosphite is decomposed by heat, the gas source flows inside the shell layer, which effectively slows down the gas release rate and enhances the gas phase flame retardant effect of melamine phosphite. The shell aluminum phosphite is heated to form a carbon layer to block the contact between the combustible gas decomposed by the plastic and the oxygen in the air, thereby blocking further combustion and effectively enhancing the flame retardant effect of the condensed phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of melamine phosphite / aluminum phosphite with a core-shell structure in Example 1;

[0032] Figure 2 is the particle size distribution diagram of melamine phosphite with different quaternary ammonium salt surfactant contents;

[0033] Figure 3 This is a particle size analysis diagram of melamine phosphite in Example 1;

[0034] Figure 4 This is a particle size analysis diagram of melamine phosphite in Example 2;

[0035] Figure 5 This is a particle size analysis diagram of melamine phosphite / aluminum phosphite with a core-shell structure in Example 1;

[0036] Figure 6 This is a thermogravimetric analysis diagram of melamine phosphite / aluminum phosphite with a core-shell structure in Example 1;

[0037] Figure 7 This is the thermogravimetric analysis diagram of melamine phosphite / aluminum phosphite with core-shell structure in Example 2. DETAILED DESCRIPTION

[0038] Example 1

[0039] (1) Preparation of dilute melamine phosphite solution

[0040] Place a round-bottom flask containing 100 ml of deionized water in an oil bath and start heating and stirring. Set the temperature to 80°C. Weigh 50 g of phosphorous acid and add it to the round-bottom flask. Weigh another 50 g of melamine and add the melamine to 100 ml of deionized water to disperse it. After the phosphorous acid is dissolved in the phosphorous acid mixed solution, add the melamine dispersion in batches. Keep the temperature of the mixed solution at 80°C and continue stirring. Add 2 g of quaternary ammonium surfactant dodecyl dimethyl benzyl ammonium chloride. After stirring for 1.5 hours, the suspension gradually becomes viscous. Add water and heat to 100°C. When the suspension becomes transparent, the reaction is complete. After cooling, filter and repeatedly wash the precipitate until the pH is neutral, and bake it in an oven at 90°C for 10 hours to obtain melamine phosphite powder. Weigh 30 g of the above powder and dissolve it in 90°C deionized water to make a 30% dilute melamine phosphite solution. Please refer to Figure 2 From the particle size diagram of melamine phosphite, it can be seen that D50 = 0.809 μm.

[0041] (2) Preparation of saturated aluminum phosphite solution

[0042] Weigh 70g of phosphorous acid and dissolve it in 120ml of water, add 45g of aluminum hydroxide, start heating and stirring, the heating temperature is 90°C, fine-tune the phosphorous acid and aluminum hydroxide content to adjust the solution to a saturated solution, and adjust the pH to 3.0. After reacting for 0.5h, add 1.5g of dispersant calcium stearate, and continue stirring for 1.5h to obtain a saturated aluminum phosphite solution.

[0043] (3) Synthesis of melamine phosphite / aluminum phosphite with core-shell structure

[0044] The dilute melamine phosphite solution of step (1) is added to the saturated aluminum phosphite solution of step (2), the temperature is controlled at 90°C, mechanical stirring is adopted, and 2.5 g of silane coupling agent KH-550 is added, the reaction temperature is increased to 105°C, stirring is continued until a white precipitate is generated, and after reacting for 2 hours, the obtained precipitate is filtered by suction, washed to pH 4.2, placed in an oven at 110°C and dried for 5 hours, transferred to a reactor with a polytetrafluoroethylene liner, placed in a muffle furnace and baked at 200°C for 3 hours, and after cooling, grinding and screening, a melamine phosphite / aluminum phosphite with a core-shell structure can be obtained, and the thermal decomposition temperature is about 428.7°C.

[0045] Depend on Figure 1 It can be seen from the scanning electron microscope that the melamine phosphite / aluminum phosphite prepared in Example 1 has an obvious core-shell structure, the outer layer of aluminum phosphite coating has a good effect, and the crystal particle size ranges from 15 to 20 μm. Figure 5 The particle size analysis chart of melamine phosphite / aluminum phosphite with core-shell structure can further verify the particle size of the product. Figure 5The data show that the D of the product obtained in Example 1 50 It is 20.27μm.

[0046] Example 2

[0047] (1) Preparation of dilute melamine phosphite solution

[0048] Place a round-bottom flask containing 100 ml of deionized water in an oil bath, turn on heating and stirring, set the temperature to 80°C, weigh 50g of phosphorous acid and add it to the round-bottom flask, weigh another 50g of melamine, add the melamine to 100ml of deionized water to disperse it. After the phosphorous acid is dissolved in the phosphorous acid mixed solution, add the melamine dispersion in batches, keep the temperature of the mixed solution at 80°C and continue stirring, add 2g of quaternary ammonium salt surfactant hexadecyltrimethylammonium chloride, continue stirring for 1.5h, the suspension gradually becomes viscous, add water and heat to 110°C, and the reaction is completed when the suspension becomes transparent. After cooling, filter and repeatedly wash the precipitate until the pH is neutral, and use an oven at 90°C to bake for 10 hours to obtain melamine phosphite powder. Weigh 30g of the above powder and dissolve it in 90°C deionized water. Make a 30% dilute melamine phosphite solution. Please refer to Figure 3 From the particle size diagram of melamine phosphite, it can be seen that D50 = 1.911 μm.

[0049] (2) Preparation of saturated aluminum phosphite solution

[0050] Weigh 70g of phosphorous acid and dissolve it in 120ml of water, add 45g of aluminum hydroxide, start heating and stirring, the heating temperature is 95°C, fine-tune the phosphorous acid and aluminum hydroxide content to adjust the solution to a saturated solution, and adjust the pH to 3.0. After reacting for 0.5h, add 0.5g of dispersant barium stearate, and continue stirring for 1.5h to obtain a saturated aluminum phosphite solution.

[0051] (3) Synthesis of melamine phosphite / aluminum phosphite with core-shell structure

[0052] The dilute melamine phosphite solution of step (1) is added to the saturated aluminum phosphite solution of step (2), the temperature is controlled at 90°C, mechanical stirring is adopted, and 2.5 g of silane coupling agent KH-550 is added, the reaction temperature is increased to 100°C, stirring is continued until a white precipitate is generated, and the obtained precipitate is filtered after reacting for 3 hours, washed to pH 4.2, placed in an oven at 110°C and dried for 5 hours, transferred to a reactor with a polytetrafluoroethylene liner, placed in a muffle furnace and baked at 200°C for 3 hours, and after cooling, grinding and screening, a melamine phosphite / aluminum phosphite with a core-shell structure can be obtained, and the thermal decomposition temperature is 446.6°C.

[0053] As a compound flame retardant, in the halogen-free flame retardant PP (APP system), 30% of APP and DiPE are added to the PP material to replace it, and the flame retardancy reaches UL94 (V0). The flame retardant performance test before and after compounding is compared, and the results are shown in Table 1 below:

[0054]

[0055]

[0056] LOI: Limiting Oxygen Index. A high index indicates that the material is not easy to burn, and a low index indicates that the material is easy to burn. It is generally believed that an oxygen index <22% is a flammable material, an oxygen index between 22% and 27% is a combustible material, and an oxygen index >27% is a flame retardant material.

[0057] Afterflame time (T1+T2): The duration of the afterflame.

[0058] UL94: Flame retardant grade.

[0059] Table 2 Mechanical properties test data of core-shell structured melamine phosphite / aluminum phosphite used in halogen-free flame retardant PP:

[0060]

[0061] From the test data in Table 1, it can be seen that when melamine phosphite / aluminum phosphite with a core-shell structure replaces 30% of APP and DiPE and is added to the PP material, the limiting oxygen index increases from 28% to 30.7%, the flame retardancy of the material is significantly increased, the vertical afterflame burning time increases by 1 second, and the flame retardancy UL94 reaches V0 level.

[0062] Table 2 shows the mechanical properties test data of the core-shell structured melamine phosphite / aluminum phosphite in Example 2 used in halogen-free flame retardant PP. From the data in the table, it can be seen that compared with the original flame retardant formula of halogen-free flame retardant PP, after replacing 30% APP, the tensile strength of the PP material remains basically unchanged, the flexural strength and flexural modulus are significantly improved, and the elongation at break increases from 18.1% to 27%.

[0063] Figure 2A1 and A2 in the figure represent the particle size distribution diagram of melamine phosphite with 2wt% and 5wt% quaternary ammonium salt surfactant added, respectively. It can be seen intuitively from the figure that when the addition amount is 2wt%, the particle size of melamine phosphite is mainly distributed between 1-2μm; when the addition amount is 5wt%, it is mainly distributed between 2-4μm. The particle size distribution of the former is smaller and more concentrated, indicating that the dispersibility of melamine phosphite is better when the addition amount of quaternary ammonium salt surfactant is 2wt%. It can be seen that the particle size of melamine phosphite can be controlled by adjusting the addition amount of quaternary ammonium salt surfactant.

[0064] The synthesis temperatures of melamine phosphite in Examples 1 and 2 were 100° C. and 110° C., respectively. Figure 3 and Figure 4 The particle size analysis chart shows that the particle size D50 of the obtained products are 0.809μm and 1.911μm respectively. In the synthesis process of melamine phosphite, the reaction temperature has a significant effect on the particle size. The particle size of melamine phosphite can be controlled by adjusting the addition amount of quaternary ammonium salt surfactant and the reaction temperature, thereby enhancing the dispersibility.

[0065] Figure 6 and Figure 7 The thermogravimetric analysis diagrams of the melamine phosphite / aluminum phosphite with core-shell structure prepared in Examples 1 and 2 are respectively. The main difference between the two products is that in the process of shelling on the surface of melamine phosphite / aluminum phosphite, the reaction temperature and time are different. The reaction temperature and time in Example 1 are 105°C for 2h, and the reaction temperature and time in Example 2 are 100°C for 3h. Figure 6 and Figure 7 The data show that the thermal decomposition temperatures of the obtained products are 428.7°C and 446.6°C respectively, and the latter has better heat resistance. Under different reaction temperatures and times, the coating rate of aluminum phosphite is different, and the thickness of the formed shell is different. The increase in reaction time at 100°C will increase the thickness of the shell, thereby increasing the decomposition temperature of the final product. The optimal reaction temperature and time need to be further explored.

Claims

1. A method for preparing a core-shell structured melamine phosphite / aluminum phosphite, characterized in that: The preparation method comprises the following steps: (1) Preparation of dilute melamine phosphite solution Step 1.1), dissolving phosphorous acid or its salt in deionized water, heating to obtain a phosphorous acid or its salt solution with a concentration of 30-50wt%, the heating temperature being 70-80°C; Step 1.2), pouring a 30-50wt% melamine aqueous dispersion into the phosphorous acid or its salt solution in batches, wherein the melamine aqueous dispersion accounts for 15-20wt%; During the reaction, 1-5 wt% of a quaternary ammonium salt surfactant is added, stirring is continued until the suspension gradually becomes viscous, water is added and the temperature is raised to 90-120°C, and the reaction is completed when the suspension becomes transparent; Step 1.3), after the obtained solution is completely cooled, it is filtered and washed until the pH value is neutral, and then dried to obtain melamine phosphite, and the drying temperature is 90-120°C; Step 1.4), dissolving the above melamine phosphite in an aqueous solution at 80-100° C. to prepare a 15-35% melamine phosphite dilute solution; (2) Preparation of saturated aluminum phosphite solution Step 2.1), dissolving phosphorous acid or its salt in a certain aqueous solution, wherein the concentration of the phosphorous acid or its salt solution is consistent with that in step 1.1); Step 2.2), adding aluminum hydroxide to the above phosphorous acid or its salt solution concentration, start heating and stirring, the weight ratio of aluminum hydroxide to phosphorous acid or its salt is 0.5-0.8:1, and the heating temperature is 70-100°C; Step 2.3), adjust the above solution to a saturated solution state, and adjust the pH to 3-3.5; Step 2.4), adding a dispersant to the saturated aluminum phosphite solution to maintain the stability of the saturated solution, with the addition amount of 0.2-2wt%; (3) Synthesis of melamine phosphite / aluminum phosphite with core-shell structure Step 3.1), adding the dilute melamine phosphite solution obtained in step (1) to the saturated aluminum phosphite solution in step (2), keeping heating and stirring, the heating temperature is 80-100°C; Step 3.2), add a coupling agent to the above solution in an amount of 0.5-2wt%, the reaction temperature is 90-110°C, and continue stirring until a white precipitate is generated; Step 3.3), the obtained white precipitate is filtered, washed to pH 4.0-4.5, and dried to obtain a white precipitate, the drying temperature is 100-180°C; Step 3.4), placing the white precipitate into a reactor lined with polytetrafluoroethylene, and baking it in a muffle furnace to solidify the core-shell structure of melamine phosphite / aluminum phosphite, the baking temperature being 200-350°C; Step 3.5), grind the obtained white powder, and screen to obtain melamine phosphite / aluminum phosphite with a core-shell structure.

2. The method for preparing the core-shell structured melamine phosphite / aluminum phosphite according to claim 1, characterized in that: The phosphite is sodium phosphite or ammonium phosphite.

3. The method for preparing the core-shell structured melamine phosphite / aluminum phosphite according to claim 1, characterized in that: The quaternary ammonium salt surfactant is one or a combination of two of hexadecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride and dialkyldimethylammonium salt.

4. The method for preparing the core-shell structured melamine phosphite / aluminum phosphite according to claim 1, characterized in that: In step 2.4), the dispersant includes at least one of barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, copper stearate, vinyl bisstearamide, and tristearic acid glyceryl.

5. The method for preparing the core-shell structured melamine phosphite / aluminum phosphite according to claim 1, characterized in that: In step 3.2), the coupling agent includes at least one of the silane coupling agents KH550, KH560, KH570, KH792, DL602, and DL-171.

6. Melamine phosphite / aluminum phosphite prepared by the method for preparing melamine phosphite / aluminum phosphite with a core-shell structure as claimed in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of spherical aluminum hypophosphite

    CN103613084A

  • Method for improving high-temperature thermal stabilization of melamine derivative flame retardant by utilizing inorganic metal phosphate, and product and application of melamine derivative flame retardant

    CN108912676A

  • High-dispersion and organic affinity aluminum phosphite flame retardant and preparation method thereof

    CN113308023A

  • Melamine hypophosphite modified lignin coated aluminum hypophosphite flame retardant as well as preparation method and application thereof in PA66 (polyamide 66)

    CN114196075A

  • Phosphorus-nitrogen synergistic composite flame retardant as well as preparation method and application thereof

    CN116622130A

Cited By

  • Efficient flame retardant based on melamine-boric acid-red phosphorus compound, preparation method and application

    CN120988364A